ANALISIS HUBUNGAN DEFISIT KESEIMBANGAN PRIMER TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Nadia Esa Putri; Muhammad Fachril Husain Jeddawi; Fadilah Risqy Utami (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2021)
The state budget is said to be healthy when it has a lower budget deficit even towards a surplus andpositive primary balance. From 2010 the Indonesian State Budget shows a budget deficit and theprimary balance has also shown a negative trend since 2012. In the case of the primary balanceand the State Budget experiencing a deficit, it can be indicated that a country’s spending exceeds itsrevenue. This expenditure issued by the government is closely related to economic growth, where theeconomic growth of a country can be measured by GDP. Keynes theory assumes that governmentintervention in the economy determines economic development can run optimally. Based on thetheory as well as previous research, it is known that there is a relationship between the primarybalance deficit on economic growth. If a country experiences a primary balance deficit, it is certain that state spending will be greater than state revenue. This means that the government is intensivelycarrying out development and stimulus to several sectors in the context of economic growth. It ishoped that the increased economic growth will reduce unemployment, increase the competitivenessof domestic products and attract investors to invest their capital. In addition to fiscal policy, there ismonetary policy adopted by Bank Indonesia in an effort to increase GDP through various monetaryinstruments, such as open market operations and standing facilities. The primary balance deficitis not a good thing because there is interest debt that must be paid and the nominal interest debtincreases every year if the budget is in deficit. In an effort to reduce the primary balance deficit,there are several steps that can be applied, including maximizing the potential of state revenueand state expenditures, saving operational costs, strict supervision of budget use, enforcement ofsecurity and order and applicable laws to restore investor confidence.